Water balance - lake water level from Stortjärn, platform, 2016-07-13–2023-09-08 - Svartberget Research Station (Swedish University of Agricultural Sciences, 2023)
Accurate measurements of the lake water level for the lakes in SITES Water.
Svartberget Research Station (2023). Water balance - lake water level from Stortjärn, platform, 2016-07-13–2023-09-08 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/k5_3AGjJmCsOnwyPDdrnmAS2
Keywords: Svartberget Research Station; Lake; Lake levels; Time instant; Time instant; Lake level; Lake level; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap